Crack coalescence mechanism of flaw pairs under biaxial loading conditions using additively printed models and photoelastic experiments. (December 2022) - Liu, Peng; Zhao, Wang; Ju, Yang; Fu, Guoming
Highlights: Crack coalescence of a 3D printed model was studied under biaxial compression. Photoelasticity was used to study the change in stress concentration at flaw tips. Shear stress concentration along the dip angle of the flaw instigates cracks. Synchronous loading constrains shear stress concentration at flaw tips. In asynchronous loading, shear cracks emerge from the flaw tips. Abstract: Revelation of the mechanism of crack coalescence is critical in understanding the failure of solids. However, specifying the mechanism of crack coalescence is challenging because the stress distribution in a complicated fracture system is complex. A visualization method using 3D printing models and photoelastic techniques was introduced to directly reveal and quantify the evolution of stress concentration at the flaw tips of flaw pairs under different biaxial loading schemes. The results indicate that the evolution of shear stress concentration at the flaw tips along the dip angle of the flaw plays a primary role in crack initiation from the flaw tips. A synchronous loading scheme significantly constrains the development of shear stress concentration at flaw tips; thus, cracks can rarely initiate. In an asynchronous loading condition, shear cracks are primarily observed emerging from the flaw tips due to the variation of shear stress concentration on the flaw tips. The propagation of shear cracks is the main cause of crack coalescence in the bridging region. This phenomenon is more significant in the scenario of a positive bridging angle.